ENT300 Bubble Printing / Azizi Sapwan... [et.al] - Sapwan, Azizi; Mahmud, Mohd Nasrul; Kadir, Adeeb Syahfienaz; Alek, Dolly Derang; Sukare, Nazatul Ikma (2015)
The business is based on partnership where it consists of four members. The members include general manager, administrative manager, operational manager, marketing manager and financial manager. The business capital is RM 13 646.00 which every shareholders contribute RM 2 729.00 for each other. Bubble Printing is a partnership business which we all start from scratch providing high quality local clothes as our products to all customers. Our target market is the adult and teenagers but the real our target is student.